2005
DOI: 10.1007/s00262-005-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic chimeric anti-endoglin (CD105) antibody: pharmacokinetics and immunogenicity in nonhuman primates and effects of doxorubicin

Abstract: We generated a human/mouse chimeric antibody c-SN6j of human IgG1 isotype from a murine anti-human endoglin (EDG) monoclonal antibody (mAb) SN6j that suppressed angiogenesis, tumor growth and metastasis in mice. We determined pharmacokinetics (PKs) and immunogenicity of c-SN6j in monkeys after multiple i.v. injections. A dose-escalation study was performed by administration of c-SN6j into six monkeys at the dose of 1 mg, 3 mg and 10 mg per kg body weight. In addition, both c-SN6j (3 mg/kg) and doxorubicin (0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…To facilitate clinical application of the anti-EDG mAbs, we generated a recombinant human/mouse chimeric mAb termed c-SN6j from SN6j. A dose escalation study of c-SN6j was performed in non-human primates to evaluate the pharmacokinetic parameters, immunogenicity and potential toxicity of c-SN6j (33). The results are very encouraging.…”
Section: Discussionmentioning
confidence: 90%
“…To facilitate clinical application of the anti-EDG mAbs, we generated a recombinant human/mouse chimeric mAb termed c-SN6j from SN6j. A dose escalation study of c-SN6j was performed in non-human primates to evaluate the pharmacokinetic parameters, immunogenicity and potential toxicity of c-SN6j (33). The results are very encouraging.…”
Section: Discussionmentioning
confidence: 90%
“…It is known that angiogenesis is crucial for tumour development and progression. Recent evidence showed that selected anti-CD105 monoclonal antibodies (mAbs) significantly inhibited the proliferation of cultured human microvascular and macrovascular endothelial cells [6], and in mouse models, certain anti-CD105 mAbs and their immuno-conjugates (conjugates with deglycosylated ricin A-chain or with 125 I) induced regression/ suppression of established tumours and inhibited growth of pre-established tumours [15]. These results support the notion that CD105 is a promising vascular target to implement innovative antibody-based therapeutic strategies in human cancer.…”
Section: Resultsmentioning
confidence: 99%
“…TRC105 concentration was determined using a validated enzyme-linked immunosorbent assay (ELISA) with a limit of quantitation of 78 ng/mL (33). …”
Section: Methodsmentioning
confidence: 99%